Revolutionizing Solar Power: Harnessing the Potential of Radio wave-Augmented Solar Cells for Clean Energy Unleashed" - George Edison (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Research at the nexus of radio wave and solar cell technology has been stimulated by the hunt for cleaner and more effective energy sources. This review article digs into the developing world of radio wave-augmented solar cells, examining the many facets that characterize the potential and difficulties of this technology. Ten topics that jointly explain the complex interrelationship between radio waves and solar cells make up the review's organizational framework. In the first section, the idea and significance of radio wave-augmented solar cells are introduced, providing light on the possibility of using radio waves as a second energy source in addition to conventional solar radiation. The investigation then focuses on the propagation characteristics and rectification mechanisms that allow the conversion of radio wave energy into usable electricity, as well as the nature of radio wave energy and how it interacts with solar cells. One of the main goals of the review is to comprehend the mechanics underlying the interaction between radio waves and solar cells. This section explains the rectification concept, which enables the conversion of alternating radio wave currents into direct current electricity and is motivated by nonlinear electrical responses within particular materials. When radio wave energy is added to conventional solar radiation to improve energy conversion, dual-energy-input systems are built on the foundation of this rectification process. After that, a comprehensive analysis of the benefits and drawbacks of radio wave-augmented solar cells follows. Extended operational windows, consistent energy generation, adaptability in application circumstances, and better energy accessibility are some of these benefits. On the other hand, issues including efficiency trade-offs, material compatibility, technical complexity, cost factors, and technological maturity present difficulties. The parts that follow examine current research, efficiency enhancements, environmental effects, and the incorporation of radio wave technologies into already-built solar infrastructure. Exploration of developments in materials science, nanotechnology, and tandem solar cell topologies highlights the possibility for increased performance and efficiency. The paper then broadens its focus to explore the larger implications of radio wave-augmented solar cells, including grid integration, commercial feasibility, and energy storage issues, in addition to environmental sustainability and energy accessibility. The review stresses possible pathways for efficiency breakthroughs, scalability, hybrid integration, and technical synergy when taking into account the technology's future possibilities. However, it also recognises problems like the development of new materials, the complexity of engineering, the precise measurement of improvements, standardization, laws, and economic feasibility. Solar cells that have been enhanced by radio waves are showing promise as a revolutionary new source of renewable energy. To fully utilize this technology, the review emphasizes the necessity of interdisciplinary cooperation, materials science innovation, engineering ingenuity, and thorough testing. Radio wave-augmented solar cells provide a glimpse into a future where varied energy sources come together to alter our approach to energy generation and pave the way for a more robust and sustainable energy environment as the worldwide search for cleaner energy grows more intense.